Do public bank guarantees affect labor market outcomes? Evidence from individual employment and wages - Laura Baessler; Georg Gebhardt; Reint Gropp; André Güttler; Ahmet Taskin (Halle Institute for Economic Research (IWH), 2024)
We investigate whether employees in Germany benefit from public bank guarantees in terms of employment probability and wages. To that end, we exploit the removal of public bank guarantees in Germany in 2001 as a quasi-natural experiment. Our results show that bank guarantees lead to higher employment, but lower wage prospects for employees after working in affected establishments. Overall the results suggest that employees do not benefit from bank guarantees.
urn:nbn:de:gbv:3:2-1054621
Keywords: E24; 330; bank guarantees; credit; employment; public banks; wages